The art of kissing : indahnya ciuman / Hugh Morris; Penerjemah, Elvira Rosa dan Alfi Kurnianingsih; Penyunting, Uswatul Chabibah. - MORRIS, Hugh; ELVIRA Rosa; ALFI Kurnianigsih; USWATUL Chabibah (Ruas, 2009)
xvi, 112 hlm. : ilus. ; 19 cm.